2022
DOI: 10.17221/58/2022-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Present and future: Does agriculture affect economic growth and the environment in the Kingdom of Saudi Arabia?

Abstract: Global climate change is a crucial environmental issue. Worldwide warming is primarily caused by carbon dioxide (CO<sub>2</sub>) emission levels. Agricultural production is among many economic activities driving CO<sub>2</sub> creation and environmental degradation. In this study, we aim to disclose the effect of agricultural production (date production) on the agricultural gross domestic product (AGDP) and the environment (CO<sub>2</sub> emissions). We collected data on dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The problem will be solved by replacing carbon mines by renewable energy sources and nuclear energy [72][73][74]. A very important role will be played by agriculture, which delivers both biomass and biogas, but also leads to environmental degradation [75].…”
Section: Discussionmentioning
confidence: 99%
“…The problem will be solved by replacing carbon mines by renewable energy sources and nuclear energy [72][73][74]. A very important role will be played by agriculture, which delivers both biomass and biogas, but also leads to environmental degradation [75].…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship between carbon dioxide emissions and agricultural productivity using the social accounting matrix (SAM) in Ethiopia was also observed [38]. In the middle east region, from the Kingdom of Saudi Arabia, an estimation by Emam found that agriculture affected the environment negatively from 1990 to 2019 period using ARDL bounds methods [39]. Data from 47 developing countries during the 1976-2017 period using dynamic panel data estimators also showed that agricultural production reduced environmental quality [40].…”
Section: Agricultural Economic Growth and Environmental Degradationmentioning
confidence: 92%
“…The information about such data is presented in Table 1. Unit root test: [61,62] state the following equation to test the order of integration of the series under study, using the ADF test:…”
Section: Data Descriptionmentioning
confidence: 99%
“…The ARDL test is efficient for small observations of time series and used irrespective of the series order I(0) and I(1) but not I(2). The following equations were used [62,63]:…”
mentioning
confidence: 99%
See 1 more Smart Citation